Phagocytosis and phagosome acidification are required for pathogen processing and MyD88-dependent responses to Staphylococcus aureus - Ip, WK Eddie (2010)
Innate immunity is vital for protection from microbes and is mediated by both humoral effectors, such as cytokines, and cellular immune defenses, including phagocytic cells such as macrophages. After internalization by phagocytes, microbes are delivered into a phagosome, a complex intracellular organelle with a well-established and important role in microbial killing. However, the role of this organelle in cytokine responses and microbial sensing is less well defined. Here we assess the role of the phagosome in innate immune sensing and demonstrate the critical interdependence of phagocytosis and pattern recognition receptor signaling during response to the Gram-positive bacteria Staphylococcus aureus. We show that phagocytosis is essential to initiate optimal MyD88-dependent response to Staphylococcus aureus. Prior to TLR-dependent cytokine production bacteria must not only be engulfed but also delivered into acidic phagosomes. Here acid-activated host enzymes digest the internalized bacteria to liberate otherwise cryptic bacterial-derived ligands that initiate responses from the vacuole. Importantly, in macrophages in which phagosome acidification is perturbed, the impaired response to Staphylococcus aureus can be rescued by addition of lysostaphin, a bacterial endopeptidase active at neutral pH that can substitute for the acid-activated host enzymes. Together these observations delineate the inter-dependence of phagocytosis with pattern recognition receptor signaling and suggest that therapeutics to augment functions and signaling from the vacuole may be useful strategies to increase host responses to Staphylococcus aureus.